Appropriate measure of unemployment in an Irish Phillips Curve - Geary, Patrick T.; Jones, Roderick M. (Economic & Social Studies, 1975)
A generalisation of the Phillips curve for a developing country, recently proposed by Modigliani and Tarentelli (1973), is modified and applied to the Irish economy for the period 1953-72 using annual data. The results indicate that a redefinition of the unemployment variable to allow for the structural characteristics of the Irish labour force fails to improve the overall fit of the Phillips relationship or the significance of the unemployment term itself. In addition, the results using unadjusted unemployment variables revealed both a small and rather weak relationship between unemployment and wage inflation, a result similar to that found by Geary and McCarthy (1975). To the extent that the rate of unemployment reflects domestic excess demand, this result provides little support for the view that Irish wage inflation is largely determined by domestic excess demand. In the context of a small open economy, this outcome is hardly surprising. The results also indicate that price expectations exercise a dominant role in determining the rate of wage inflation in Ireland; whether quarterly or monthly data would produce a more significant role for domestic factors such as the structure of the labour force is open to question.
Keywords: Irish Economy; Philips curve